If x is a real number satisfying x 3 − x 3 1 = 1 4 , compute x − x 1 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Very nice! Did the same.
cool, same way.
I try to explain this to my friend, yet he doesn't understand.
Can you guys ( expecially Risabh Cool and Abhay Kumar ) help me to tell my friend with your clear own word
This is his question :
How you find t 3 + 3 t − 1 4 = ( t − 2 ) ( t 2 + 2 t + 7 ) ?
Please give me a clear and understand word, so I can teach my friend
Log in to reply
(X^3 + 3X - 14) = 0 Let this expression be f(X) Find values of X when f(X) = 0 by trial and error. Generally you would get a value within few tries. For example try f(–1), f(1), f(2), f(–2) You should get a value for X when f(X) = 0 by now. In this case, when X = 2, f(X) = 0. Therefore (X–2) is a factor of the equation. Now follow me: (X–2)*(AX^2 + BX + C) + D = (X^3 + 3X – 14) This is how we find the factors of a higher order polynomial. For finding a cubic polynomial, multiply the linear factor with a general quadratic factor so that you'll get your highest power as '3'. Now you need to expand the polynomial so that you will get the coefficients of X^3, X^2, X, and the constant in the terms of A, B, C, D. After simplifying it, just compare the coefficients on the LHS with the RHS and you'll get the desired solution! ;) Voilà!
Log in to reply
thx, ur explanation is more explainable
Let x − x 1 = a then cubing both sides we get ( x − x 1 ) 3 = a 3 x 3 − 3 . x 2 . x 1 + 3 . x x 2 1 − x 3 1 = a 3 x 3 − x 3 1 − 3 ( x − x 1 ) = a 3 1 4 − 3 a = a 3 By inspection it is clear that a = 2 is solutions so a − 2 is a root ⇒ ( a − 2 ) ( a 2 + 2 a + 7 ) = 0 ∴ x − x 1 = 2 ( ∵ x − x 1 ∈ R )
Problem Loading...
Note Loading...
Set Loading...
1 4 = x 3 − x 3 1 = ( x − x 1 ) 3 + 3 ( x − x 1 ) P u t x − x 1 = t ⇒ t 3 + 3 t − 1 4 = 0 ⇒ ( t − 2 ) ( t 2 + 2 t + 7 ) = 0 ⇒ x − x 1 = t = 2